Dual-passivation of ionic defects for highly crystalline perovskite. (February 2020) - Si, Haonan; Xu, Chenzhe; Ou, Yang; Zhang, Guangjie; Fan, Wenqiang; Xiong, Zhaozhao; Kausar, Ammarah; Liao, Qingliang; Zhang, Zheng; Sattar, Abdul; Kang, Zhuo; Zhang, Yue
Abstract: The ionic defects in hybrid halide perovskite materials served as the recombination center severely restricts its application for solar cells. Here, we proposed a dual-passivation strategy via simply incorporating low-cost ammonium chloride to simultaneously passivate negative- and positive-charged ionic defects, as indicated by first-principles density functional theory calculation. The efficient defect modulation reduces the defect density and prolongs the carrier lifetime, thereby contributing to the highly crystalline perovskite, which is demonstrated by light-dependent kelvin probe force microscopy, transient absorption and visualized fluorescence lifetime imaging microscopy. Benefiting from these merits, the power conversion efficiency of perovskite solar cells is boosted up to 21.38%. More importantly, this dual-passivation approach can be further extended to mixed-cation perovskite systems, not limited in traditional methylammonium based perovskite only. Such methodology of simultaneously regulating ionic defects in different types may probably give impetus to effectively promote perovskite evolution. Graphical abstract: Image 1 Highlights: The dual-passivation strategy was proposed to simultaneously modulate both negative- and positive-charged ionic defects. The highly crystalline perovskite was obtained, thereby contributing to the evaluated PV performance up to 21.38%. The dual-passivation strategy is feasible to traditional MA-based perovskite but also to mixed-cation perovskite systems.